2022
DOI: 10.1097/ncc.0000000000001054
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Needs of Caregivers of Adult Patients With Hematologic Malignancies During Treatment

Abstract: Background: Family caregivers play a vital role in providing care and support for patients with life-threatening hematologic diseases. Extensive patient care needs and long-term treatment trajectories can negatively affect the health of caregivers. Despite the importance of supporting caregivers, few studies examine family caregivers' experiences and support needs during treatment. Objective: To explore the role, experiences, and needs of family caregivers of patients with hematologic malignancies during treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is also reported that being a caregiver of and caring for a person with a life-threatening, non-malignant, chronic illness can be a burden and negatively influence the caregiver's own everyday life, quality of life, health, and well-being [15][16][17]. It is also well known from cancer research that the emotional handling of illness by the ill person and caregiver does not seem to be independent of each other [18,19] meaning that illness can also be limiting for the caregivers' life and activities [20,21]. Caregiving, although at times experienced as emotionally rewarding [3], might as such be stressful [4] and caregivers are described in the scientific literature as a "hidden patient group" [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that being a caregiver of and caring for a person with a life-threatening, non-malignant, chronic illness can be a burden and negatively influence the caregiver's own everyday life, quality of life, health, and well-being [15][16][17]. It is also well known from cancer research that the emotional handling of illness by the ill person and caregiver does not seem to be independent of each other [18,19] meaning that illness can also be limiting for the caregivers' life and activities [20,21]. Caregiving, although at times experienced as emotionally rewarding [3], might as such be stressful [4] and caregivers are described in the scientific literature as a "hidden patient group" [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that being a caregiver of and caring for a person with a life-threatening, non-malignant, chronic illness can be a burden and negatively influence the caregiver's own everyday life, quality of life, health, and well-being [15][16][17]. It is also well known from cancer research that the emotional handling of illness by the ill person and caregiver does not seem to be independent of each other [18,19] meaning that illness can also be limiting for the caregivers' life and activities [20,21]. Caregiving, although at times experienced as emotionally rewarding [3], might as such be stressful [4] and caregivers are described in the scientific literature as a "hidden patient group" [15].…”
Section: Introductionmentioning
confidence: 99%